2014
DOI: 10.1097/jto.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Bcl-2 Depends on Tumor Histology and Expression of MALAT-1 lncRNA in Non–Small-Cell Lung Cancer

Abstract: Bcl-2 expression was specifically associated with superior prognosis in localized NSCLC. An interaction of Bcl-2 with MALAT-1 lncRNA expression was revealed, which merits further investigation for risk prediction in resectable NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 46 publications
1
39
0
1
Order By: Relevance
“…Some lncRNAs, for instance, PCAT1, PCGEM1, MALAT1, are reported to be potential therapeutic targets for PCa . In this study, we first found that TMPO‐AS1 was up‐regulated in PCa samples and was regulated by AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some lncRNAs, for instance, PCAT1, PCGEM1, MALAT1, are reported to be potential therapeutic targets for PCa . In this study, we first found that TMPO‐AS1 was up‐regulated in PCa samples and was regulated by AR.…”
Section: Discussionmentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs), transcripts longer than 200 nucleotides without protein translation, have been observed to function in carcinogenesis . Some can work as clinically relevant biomarkers since being linked to prognosis . Recent researches have suggested lncRNAs related to AR signaling pathways and played functions in the PCa progression .…”
Section: Introductionmentioning
confidence: 99%
“…In NSCLC, Bcl-2, Bcl-xl and Mcl-1 are often found to be upregulated, which is associated with chemotherapy resistance and metastasis of cancers [11, 12]. These findings indicate that suppression of the anti-apoptotic Bcl-2 proteins may be a promising strategy for cancer therapy and potentially overcome the resistance to conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, in gastric cancer [12] and cutaneous Merkel cell carcinoma [13], Bax expression is obviously increased, while which decrease in colorectal cancer [14] and nasopharyngeal carcinoma [15]. As reported in nonsmall cell lung cancer [16], patients with Bcl-2 overexpression have poor clinical prognosis. In oral squamous cell carcinoma [17], patients with Bax-positive expression have a better prognosis.…”
Section: Introductionmentioning
confidence: 89%